Developmental alterations in noxious-evoked EEG activity recorded from rat primary somatosensory cortex - Devonshire, Ian M.; Greenspon, Charles M.; Hathway, Gareth J. (Elsevier, 2015)
Primary somatosensory cortex (S1) contains a nociceptive map that localizes potential tissue damage on the body and encodes stimulus intensity. An objective and specific biomarker of pain however is currently lacking and is urgently required for use in non-verbal clinical populations as well as in the validation of pre-clinical pain models. Here we describe studies to see if the responses of the primary somatosensory cortex (S1) in juvenile rats are different to those in the adult. We recorded EEG responses from S1 of lightly-anaesthetised Sprague-Dawley rats at either postnatal day 21 or postnatal day 40 during the presentation of noxious (550C) or innocuous (300C) thermal stimuli applied to the plantar surface of the left hindpaw. The total EEG power across the recording period was the same in both ages after stimulation but the frequency distribution was significantly effected by age: noxious heat evoked a significant increase in theta band (4-8 Hz) activity in adults only (P<0.0001 compared to baseline; P<0.0001 compared to juveniles). There were no significant differences in EEG responses to innocuous thermal stimuli. These data show that there are significant alterations in the processing of nociceptive inputs within the maturing cortex and that cortical Theta activity is involved only in the adult cortical response to noxious stimulation.